Media Film Hallo Aus Berlin dalam Peningkatan Penguasaan Kosa Kata Bahasa Jerman - Siti Ermi Nati; Ambo Dalle (Phonologie : Journal of Language and Literature, 2022)
Abstract. This study aims to determine the improvement, planning, process, and results of using the film media Hallo aus Berlin in increasing the mastery of German vocabulary in class XI SMAN 2 Makassar. This type of research is classroom action research which consists of two cycles. The subjects in this study were students of class XI SMAN 2 Makassar. The data analysis technique in this study consisted of qualitative and quantitative data. Qualitative data was obtained through observation, while quantitative data was obtained through vocabulary mastery tests in cycle I and cycle II. Data analysis using the percentage technique. The results showed that the increase in vocabulary mastery with the average score obtained by students in the first cycle reached 66.94%, and the second cycle reached 78.19%. These results indicate that the use of the film Hallo aus Berlin media can improve the mastery of German vocabulary in class XI SMAN 2 Makassar.Keywords: Improvement, Hallo Aus Berlin Film Media, Vocabulary Mastery